Impact of device pass count and reperfusion levels in anterior circulation stroke: differential effects based on large-scale data from clinical practice - Meucci, Luca; Meyer, Lukas; Broocks, Gabriel; Bechstein, Matthias; Thaler, Christian; Heitkamp, Christian; Winkelmeier, Laurens; Geest, Vincent; Heitkamp, Alexander; Jungnitz, Maximilian; Gregor, Peter; Schlicht, Felix; et al. (Journal of neurology, 2025)
The relationship between angiographic success, number of device passes and functional outcome is a topic of clinical interest in endovascular thrombectomy (EVT) for acute ischemic stroke (AIS). This study systematically assessed differential effects of reperfusion levels and device pass counts based on large-scale, multicenter registry data.